How to Analyze (Intentional) Consciousness in Terms of Meta-Belief and Temporal Awareness - Beyer, Christian (Frontiers in Psychology, 2018)
The paper presents and defends a metadoxastic view on (intentional) consciousness that is novel in four respects: (1) It is motivated both by Husserl's dynamic approach, which looks upon mental acts as momentary components of certain cognitive structures – “dynamic intentional structures” – in which one and the same object is intended throughout a period of time (during which the subject's cognitive perspective upon that object is constantly changing) and by his conception of consciousness in terms of internal time-consciousness (temporal awareness). (2) It combines a dispositionalist higher-order judgement theory about the structure of (intentional) consciousness with the claim that the contents of these judgements are such that they can be expressed by essentially indexical sentences containing the temporal indexical “now”, thus accommodating the basic role of internal time-consciousness. (3) It is immune against the “objection from lack of mental concepts” raised, e.g., by Dretske against any higher-order representation theory, as it employs counterfactuals in the framework of a disjunctive account of (intentional) consciousness. (4) It explains the unity of consciousness at a time as well as across time.